2021
DOI: 10.1093/bjsopen/zrab134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative acute kidney injury in patients undergoing major gastrointestinal surgery on 1-year survival and renal outcomes: a national multicentre cohort study

Kenneth A McLean,
Sivesh K Kamarajah,
Emily Mills
et al.

Abstract: Background The intermediate-term impact of acute kidney injury (AKI) in patients after major gastrointestinal and liver surgery has not been well characterized. This study aimed to evaluate the 1-year mortality rate and renal outcomes associated with postoperative AKI in a national prospective cohort. Methods This prospective multicentre, observational cohort with 1-year postoperative follow-up included adults undergoing majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Whilst our study is unable to establish a causal relationship between complications and long-term healthcare use given the potential for unmeasured confounding, it adds to the substantial literature demonstrating the poor long-term health outcomes associated with postoperative complications. 8 12 , 13 , 14 27 Our data highlight the attention provided in primary care before and after surgery. Whilst the largest relative change in healthcare encounters was within secondary care, primary care still accounted for most encounters, even amongst patients with complications.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Whilst our study is unable to establish a causal relationship between complications and long-term healthcare use given the potential for unmeasured confounding, it adds to the substantial literature demonstrating the poor long-term health outcomes associated with postoperative complications. 8 12 , 13 , 14 27 Our data highlight the attention provided in primary care before and after surgery. Whilst the largest relative change in healthcare encounters was within secondary care, primary care still accounted for most encounters, even amongst patients with complications.…”
Section: Discussionmentioning
confidence: 60%
“… 4 5 Less frequent and more serious complications include myocardial infarction and acute kidney injury. 6 , 7 , 8 , 9 , 10 Patients with complications after surgery have a greatly increased risk of death during their hospitalisation. 3 However, even those who survive the immediate affects of the complication have substantially reduced long-term survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Elderly individuals, especially when affected by comorbid conditions, are more prone to developing AKI ( 20 ). Factors such as infections, heart failure, hypertension, gastrointestinal bleeding, surgical procedures, and urologic stones are predisposing elements that can easily induce AKI ( 21 , 22 ). Therefore, early diagnosis and intervention hold paramount significance in preventing postoperative AKI in elderly patients undergoing abdominal surgeries, with far-reaching implications for reducing societal and family healthcare expenditures.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative AKI is associated with CKD progression and increased late mortality after cardiac and other organ surgery 42. The STARSurg Collaborative43 recently confirmed that postoperative AKI in patients undergoing gastrointestinal surgery increased mortality after 1 year of observation. The role of AKI in the causal relationship with mortality has not been established.…”
mentioning
confidence: 99%